Vascular Dementia Patients Characteristics With a History of Stroke in a National Brain Center Hospital Jakarta, Indonesia - Hanifah, Afifah Kusuma; Astari, Riezky Valentina; Muktamiroh, Hikmah; Saleh, Arman Yurisaldi (Folia Medica Indonesiana, 2022)
Highlights: • Characteristics of vascular dementia patients with a history of stroke was aimed. • The most characteristics of vascular dementia patients with stroke history are men, post-ischemic stroke, hypertension grade 1, and lesions in the basal ganglia. Abstract: Stroke patients increase each year. Stroke is a cerebrovascular disorder caused by disruption of cerebral blood flow, which could reason vascular lesions within the mind parenchyma to be a threat to significant disorders. One of them is vascular dementia. Each affected person is prone to growing dementia after a stroke in three to five instances. Thisstudy aimed to decide the traits of patients with vascular dementia with a record of stroke. This study used a descriptive retrospective approach with a cross-sectional method. The samples were obtained from the total sampling technique. The sample of the study was vascular dementia patients with a stroke record at the National Brain Center Hospital Prof. Dr. dr. Mahar Mardjono Jakarta in the period of 2020 through the inclusion standards with 191 samples. This study found that the majority of patients were males as many as 129 (67.5%), age group of 55-64 were 67 patients (35.1%), post-ischemic strokes were 164 patients (85.9%), grade 1 hypertension as many as 70 patients (36.6%), and basal ganglia as many as 76 patients (29.23%). Characteristics of vascular dementia patients with the maximum stroke records in men, aged 55-64 years, post-ischemic stroke, grade 1 hypertension, and a majority of the lesions within the basal ganglia.